2021
DOI: 10.1371/journal.pone.0244974
|View full text |Cite
|
Sign up to set email alerts
|

Reduced social distancing early in the COVID-19 pandemic is associated with antisocial behaviors in an online United States sample

Abstract: Antisocial behaviors cause harm, directly or indirectly, to others’ welfare. The novel coronavirus pandemic has increased the urgency of understanding a specific form of antisociality: behaviors that increase risk of disease transmission. Because disease transmission-linked behaviors tend to be interpreted and responded to differently than other antisocial behaviors, it is unclear whether general indices of antisociality predict contamination-relevant behaviors. In a pre-registered study using an online U.S. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 60 publications
8
45
0
1
Order By: Relevance
“…In support of the observational findings by O'Connell et al (2021) 3 , Carvalho and Machado (2020) 4 , and Nivette et al (2020) 5 , the positive genetic correlation between ASB and Covid-19 suggests that individuals who engage in ASB appear more susceptible to Covid-19 than those who do not engage in ASB. This implies they may put themselves and others at higher risk and/or that the health conditions associated with ASB, such as chronic obstructive pulmonary disease, make those prone to ASB an at-risk group for Covid-19.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In support of the observational findings by O'Connell et al (2021) 3 , Carvalho and Machado (2020) 4 , and Nivette et al (2020) 5 , the positive genetic correlation between ASB and Covid-19 suggests that individuals who engage in ASB appear more susceptible to Covid-19 than those who do not engage in ASB. This implies they may put themselves and others at higher risk and/or that the health conditions associated with ASB, such as chronic obstructive pulmonary disease, make those prone to ASB an at-risk group for Covid-19.…”
Section: Discussionsupporting
confidence: 52%
“…Concerning how ASB may abet pandemic spread, O’Connell et al . (2021) reported that those in an online US cohort who engaged more in ASB also more frequently ignored Covid-19 social-distancing measures 3 . Likewise using an online cohort, Carvalho and Machado (2020) found that those with increased psychopathic traits and low levels of empathy tended to adhere less to Covid-19 containment measures 4 .…”
mentioning
confidence: 99%
“…Several studies have also examined the more maladaptive aspects of personality including antisociality, negative affect, detachment, antagonism, and disinhibition. Here, the findings are clear: higher levels of maladaptive traits are related to less compliance with public-health measures (Miguel et al, 2020;Roma et al, 2020;O'Connell et al, 2021). Turning to the specific traits of the Dark Triad, Nowak et al (2020) find that all three traits are related to engaging in fewer preventative measures.…”
Section: Part 1: Personality and Covid-19 Compliancementioning
confidence: 87%
“…In the initial absence of an effective vaccine, the virus could only be managed by isolation and quarantining of the positive/suspected cases, social (physical) distancing, wearing of facemasks, regular hand-washing, and using sanitizers. Studies have shown a considerable part of people's compliance with these measures to be dependent on their personality traits (Carvalho et al, 2020;Oosterhoff & Palmer 2020;Miguel et al, 2021;Murphy et al, 2021;O'Connell et al, 2021). Therefore, the purpose of the present study was to explore various personality characteristics in an Indian student sample between those who took the virus as a serious threat and those who did not.…”
Section: Discussionmentioning
confidence: 93%
“…Murphy et al (2021) found people with lower levels of conscientiousness were also more likely to be hesitant or resistant to be vaccinated. O'Connell et al (2021) showed that people with lower levels of agreeableness, higher levels of Machiavellianism (manipulative behavior), psychopathy, and narcissism were less likely to comply with COVID-19 prevention measures. Miguel et al (2021), as noted earlier, found that the antisocial traits of deceitfulness, callousness, risk-taking, and lower levels of empathy were directly correlated with lower compliance to COVID-19 restrictions.…”
Section: Introductionmentioning
confidence: 99%